Physicochemical properties and biological activities of Thai plant mucilages for artificial saliva preparation - Aranya Manosroi (2018)
© 2015 Informa Healthcare USA, Inc. Context: Plant mucilages can be found in various parts of several Thai plants, which can be used as thickening, moisturizing, and lubricating agents in artificial saliva formulations. Objective: The objective of this study was to evaluate the physicochemical properties, biological activity, and cytotoxicity of Thai plant mucilages. Materials and methods: The mucilages from Thai plants were extracted by various processes (temperature and pH variation, microwave oven, steam, and Tris-HCl buffer extraction). The viscosity and the rheology were evaluated using viscometer. Antioxidative activities including DPPH radical scavenging and metal chelating activities were investigated. The mucilages were determined for cytotoxicity on normal human gingival fibroblasts and anti-adherent activity of Streptococcus mutans. Results: Mucilages from Ocimum citriodorum Vis. (Lamiaceae), Artocarpus heterophyllus Lam. (Moraceae), Abelmoschus esculentus (Linn.) Moench. (Malvaceae), and Basella alba Linn. (Basellaceae) exhibited pseudoplastic non-Newtonian rheology. The highest DPPH radicalscavenging and metal-chelating activities were observed in the mucilages from B. alba (microwave, 3 min) and A. esculentus (microwave, 1 min) with the SC 50 and MC 50 values (50% of scavenging activity and 50% of metal chelating activity, respectively) of 0.71 ± 0.32 and 1.11 ± 0.52 mg/ml, respectively. Most mucilages exhibited no cytotoxicity to normal human gingival fibroblasts. The mucilage from A. esculentus (microwave, 5 min) gave the shortest wetting time of 2.75 ± 0.51 min. The highest S. mutans adhesion inhibition was observed in A. esculentus (pH 11) of 5.39 ± 9.70%. Discussion and conclusion: This study has indicated the suitable physicochemical and biological properties and the potential application of mucilages from Thai plants for artificial saliva preparation.